Effects of Combined Resistance-Aerobic Training and Milk Consumption on the Weight Loss of Overweight Female Students - Asadi, Amin; Ghasemi, Mohammad; Zarandi, Ehsan; Khanjari, Mohammad Mahdi; Bayat, Sahar; Malekmohammadi, Samaneh (International Journal of Sport Studies for Health, 2019)
The purpose of this study was to determine the effect of milk consumption following resistance-aerobic training on the weight loss of female students. Information was collected from 80 female students with more than 10 kg overweight in the body composition analysis. Forty eligible students were then randomly divided into two groups of aerobic-resistance training and aerobic-resistance training plus milk consumption. Finally, a total of 30 students remained in the study. The students consumed milk immediately and one hour after aerobic-resistance training. The exercise protocol included aerobic-resistance exercises for six weeks (three days a week). The results of independent t-test after six weeks of aerobic-resistance training showed a significant reduction in weight loss indicators, including body fat percentage (P = 0.04), total body fat (P = 0.03), and waist-to-hip ratio (P = 0.03), in addition to an increase in muscle gain (P = 0.002) in the exercise + milk group, compared to the aerobic-resistance training group. Therefore, it seems that a resistance-aerobic training program, along with milk consumption, can improve the body composition and health indicators of individuals.